Effects of changeover delay on response allocation during probe tests. Issue 2 (23rd August 2013) - McDevitt, Margaret A.; Bell, Matthew C.
<x xml:space="preserve">Abstract</x> The present study assessed whether a pattern of responding that develops when choosing between two alternatives generalizes to novel choice tests when alternatives are presented in new combinations. Pigeons were trained on a two‐component multiple schedule. In both components, a concurrent variable‐interval (VI) 40‐s VI 80‐s schedule was used. The COD was 1 s in one component and 10 s in the other. The long COD produced consistently longer dwell times than the short COD did. Following training, subjects were presented with four types of probe‐test components in which one alternative was drawn from the component with the short COD and one alternative was drawn from the component with the long COD. When the schedule values of the two alternatives were identical (VI 40 vs. VI 40 and VI 80 vs. VI 80), subjects preferred the alternative trained with the long COD (Ms = .78 and .61, respectively). Additionally, subjects preferred the VI 40‐s alternative trained with the long COD to the VI 80‐s alternative that was trained with the short COD (M = .85). Systematic preference was not observed when subjects were given a choice between the VI 40‐s alternative that was trained with the short COD and the VI 80‐s alternative that was trained with the long COD. These results demonstrate that a stimulus associated with a longer COD, and thus longer dwell times in baseline training, may be more preferred during probe tests than expected on the basis of the rate of primary reinforcement associated with that stimulus.